Effects of a Flexible Workout System on Performance Gains in Collegiate Athletes. Issue 5 (May 2021) - Walts, Cory T.; Murphy, Sabrina M.; Stearne, David J.; Rieger, Randall H.; Clark, Kenneth P.
Abstract : Abstract: Walts, CT, Murphy, SM, Stearne, DJ, Rieger, RH, and Clark, KP. Effects of a flexible workout system on performance gains in collegiate athletes. J Strength Cond Res 35(5): 1187–1193, 2021—Although research on the topic of periodization is abundant, investigations into different flexible periodization strategies in collegiate athletes are limited. Furthermore, how state of readiness (SOR) and workout autonomy affect training improvements is largely unknown. Therefore, the purpose of this study was to determine if a flexible periodization (FP) program would elicit significantly greater performance gains compared with a nonflexible periodization (NP) program (significance set p ⩽ 0.05). A total of 32 male and female intercollegiate lacrosse players completed performance measures of vertical jump, sprinting speed, change of direction, and strength in bench press and deadlift. After pretesting, subjects were matched and randomly assigned to either FP ( n = 17, age = 19.4 ± 1.4 years, height = 1.72 ± 0.10 m, mass = 72.29 ± 13.73 kg) or NP ( n = 15, age = 19.9 ± 1.5 years, height = 1.72 ± 0.08 m, mass = 71.68 ± 13.55 kg) training groups. Both groups trained 3 days per week for 8 weeks. The NP group completed all workout volume and intensity as prescribed by a certified strength and conditioning coach. However, the FP group modified workout volume and intensity based on a daily SOR questionnaire. Although appreciable pretest to posttest improvements were observed for the entire subject cohort, multivariate analysis of variance (ANOVA) and a series of ANOVA tests demonstrated no statistically significant between-group differences for pretest to posttest changes on any of the performance tests (range of p values: 0.17–0.95). Although FP does not seem to be more effective than NP for eliciting performance gains, it may provide greater opportunities for autonomy while eliciting equivalent improvement levels. Therefore, flexible periodization based on SOR may be a viable training strategy.